2011
DOI: 10.1021/la105126n
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Enhanced Nonlinear Magnetophoresis for High-Resolution Bioseparation

Abstract: A new mode of transport is described that was capable of high-resolution separation of superparamagnetic materials from complex mixtures based on their size. Laminar flow and a rotating external magnetic field were applied to superparamagnetic beads assembled on a semiperiodic micromagnet array. Beads at the edge of the micromagnet array oscillated in-phase with the external magnetic field with an amplitude that decreased with increasing frequency, ω, until they reached an immobilization frequency, ωi, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…The micro-magnets were composed of 5.0 m diameter and 100 nm thick cobalt discs that were deposited on a silicon substrate on 8.0 m centre-to-centre distance. 14,17 This MMA configuration allowed the beads to be 70 transported in the x direction to the edges of the micro-magnets array by a rotating external magnetic field, and separation occurred at the edge of the arrays in the y direction due to hydrodynamic forces. The electromagnet system was driven with an externally programmed frequency, ω, in a four phase cycle as 75 described previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The micro-magnets were composed of 5.0 m diameter and 100 nm thick cobalt discs that were deposited on a silicon substrate on 8.0 m centre-to-centre distance. 14,17 This MMA configuration allowed the beads to be 70 transported in the x direction to the edges of the micro-magnets array by a rotating external magnetic field, and separation occurred at the edge of the arrays in the y direction due to hydrodynamic forces. The electromagnet system was driven with an externally programmed frequency, ω, in a four phase cycle as 75 described previously.…”
Section: Methodsmentioning
confidence: 99%
“…5,[17][18][19][20][21] This has limited HGM to dilute solutions in which bead-bead interaction are unlikely to occur. FEM calculations of the local magnetic field on the MMAs, as shown in Figure 1B, revealed that the SPM beads produce little change in the local magnetic field and thus the SPM beads do not interact with each other to 5 form chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size and magnetisationbased separation can be achieved by increasing the frequency of the travelling magnetic field to a speed where the hydrodynamic force exceeds the magnetic force. [18][19][20][21] A critical frequency, , exists for a SPM bead…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Moreover, arrays of cobalt micro-magnets in combination with a rotating external magnetic field have been used for the magnetophoretic transportation of magnetic beads, and their ability to separate beads with different magnetophoretic mobilities by tuning the frequency of the applied magnetic field has been demonstrated. [15][16][17] Previously, we have shown that magnetic beads can be selectively transported between stripes on a chip with periodic arrays of long exchange-biased permalloy microstripes using a rotating external magnetic field. 18 Recently, the use of a continuous film with a periodic array of exchange-biased stripes with alternating magnetization orientations induced by ion bombardment was also presented.…”
Section: Introductionmentioning
confidence: 99%